High-Magnetic-Field-Induced First-Order Magnetic Transition and Tricritical Phenomenon in Antiferromagnetic Semimetal NdSb - Zhao, Jun; Rahman, Azizur; Liu, Wei; Ling, Langsheng; Han, Yuyan; Xi, Chuanying; Pi, Li; Qu, Zhe; Gao, Hao; Zhang, Lei (Chinese physics letters, 2025)
The antiferromagnetic (AFM) semimetal NdSb is well known for the interplay between its exotic magnetism and topological properties. However, its magnetism remains poorly understood. In this study, we thoroughly investigated the magnetization of NdSb single crystals with a high magnetic field ( H ) of up to 30 T applied in various directions. We found that the AFM phase is suppressed by a magnetic field of 9.41 T when H ∥ [100] and 11.25 T when H ∥ [110], whereas the suppression field ranges from 9.41 to 10.67 T with a hysteresis of 1.26 T when H ∥ [111]. The magnetization of H ∥ [100], which is an easy direction with a typical magnetic transition, was studied in detail. The AFM phase with H ∥ [100] was suppressed at lower temperatures, disappearing at approximately 6.25 K. The critical exponents β = 0.234(3), γ = 0.824(6), and δ = 4.90(6) were obtained for H ∥ [100], and aligned with a tricritical mean-field model. Analysis of the critical behavior suggests a field-induced tricritical phenomenon for H ∥ [100]. An H – T phase diagram for an NdSb single crystal was constructed for H ∥ [100], revealing a field-induced first-order transition and a tricritical point (TCP) at T tr = 6.25 K and H tr = 9.41 T. The clarification of the multiple magnetic phases and transitions in NdSb provides crucial insights into the correlation between its magnetism and topology.